Fashion, Society, and the First World War International Perspectives - Bass-Krueger, Maude; Edwards-Dujardin, Hayley; Kurkdjian, Sophie (Bloomsbury Academic, 2021)
This book is the first of its kind to study the impact that the Great War had on fashion, the fashion industry and civilians in a transnational context.